Middelalderbyen Oslo - av stokk og stein - Stige, Morten; Bauer, Egil Lindhart (Collegium Medievale, 2019)
The general impression from the literature on medieval Oslo is that the townscape was dominated by timber buildings, the only major exceptions being the buildings of the Church and the King. When the remains of a large stone building outside the Bishops palace was discovered by NIKU in 2013, it was accordingly presumed to be from the sixteenth century. The size of the building made Byantikvaren undertake a documentation which led to samples being taken, dating it to c 1300. This has led to a new and more critical approach to excavated stone buildings in Oslo. This article reassesses earlier archaeological material and diplomas and concludes that stone buildings were probably to be found on most properties by the end of the fourteenth century.